Analisis Pengaruh Kinerja Keuangan terhadap Harga Saham pada Perusahaan Index Lq45 yang Terdaftar pada Bursa Efek Indonesia (BEI) Periode 2019-2023 (Jurnal Kendali Akuntansi, 2025)
This study aims to determine the effect of liquidity ratios as proxied by the Current Ratio and Quick Ratio, solvency ratios as proxied by the Debt to Asset Ratio and Debt to Equity Ratio, and profitability ratios as proxied by Return On Assets and Return On Equity. Based on the type and nature of the data used in this study, it is quantitative. The data analysis technique in this study begins with descriptive statistical analysis. The analysis is then continued with a panel data regression analysis, taking into account the coefficient of determination (R² test), model feasibility (F test), and the significance of the independent variables on the dependent variable (t-test). Data analysis in this study was conducted using the Econometric Views (EViews) program. The results of the study indicate that: 1) the Current Ratio has a negative and insignificant effect on stock prices, while the Quick Ratio has a positive and significant effect on stock prices; 2) DAR has a negative and significant effect on stock prices, while DER has a positive and insignificant effect on stock prices; and 3) ROA has a positive and significant effect on stock prices, while ROE has a negative and insignificant effect on stock prices.